Painéis de partículas de madeira leucena e resina poliuretana derivada de óleo de mamona - da Silva, Sergio Augusto Mello [UNESP]; Christoforo, André Luis; Panzera, Túlio Hallak; de Almeida, Diego Henrique; Segantini, Antônio Anderson da Silva [UNESP]; Lahr, Francisco Antonio Rocco (FapUNIFESP (SciELO), 2013)
This research aimed to test particleboard with leucena (Leucaena leucocephala) wood particles and polyurethane resin castor oil based. The response variables are: modulus of rupture (MOR), internal adhesion (AI), apparent density (dap) and wood moisture content (um). The experiments were developed based on the methodological procedures of the ABNT NBR 14810:2002 standard. The particleboards were manufactured by hot-pressing at 4MPa and 90°C, using timber particles with 5% of moisture content and 10% of monocomponent and bicomponent polyurethane resin. The higher moisture content was achieved when the monocomponent polyurethane resin was used. The bicomponent polyurethane resin provided a percent increase of 43.7% and 22.7% on the modulus of rupture and apparent density, respectively, when compared to the standard limit. The internal adhesion of the panels manufactured with monocomponent resin was 2.45 times higher than the standard limit. The confidence interval between means revealed that the internal adhesion and apparent density exhibited statistical equivalence. A good correlation between the internal adhesion and apparent density was found, for this reason it was possible to estimate the internal adhesion of the panels based on the apparent density data.
Particleboard manufactured with leucena wood and polyurethane resin castor oil based
Keywords: Bending; Internal adhesion; Moisture content; Strength